Cascaded PI Controller Tuning for Power Plant Superheated Steam Temperature based on Multi-Objective Optimization. Issue 1 (July 2017) - Fu, H.; Pan, L.; Xue, Y.L.; Sun, L.; Li, D.H.; Lee, K.Y.; Wu, Z.L.; He, T.; Zheng, S.
Abstract: To improve the superheated steam temperature (SST) control performance, this paper considers the conflicting objectives in SST control, multi-objective optimization (MOO) algorithm is employed in this paper. Firstly, the inner-loop PI controller is optimized by considering the objectives of set-point tracking and disturbance rejection, with and without constraints on robustness level. It is found that robustness constraint is essential in the optimization. Secondly, the regulation performance of the outer-loop PI controller is addressed by optimizing the disturbance rejection and robustness simultaneously. The parameter are determined based on the simulation comparison between the non-dominated solutions. The simulation results demonstrate a promising prospect of promoting the proposed strategy to more industrial practices.